1987
DOI: 10.2307/1591032
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effects of Low Levels of Ochratoxin A in Ovo: Utilization of a Chicken Embryo Model

Abstract: Ochratoxin A (OA) was administered to 13-day-old chicken embryos via the chorioallantoic membrane. The 7-day LD50 value (day 20 incubation) of OA was calculated at 7.9 micrograms of OA. Ochratoxin-treated embryos (2.5 micrograms) had slight but significant changes in numbers of immunoglobulin-bearing cells in the bursa but not in the spleen. Chicks hatched from in ovo-treated eggs were challenged with 9 X 10(4) colony-forming units (CFU) of beta-hemolytic Escherichia coli (O1:K1) at 7 days of age via the thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…This meant that each bird consumed 160 and 320 µg of OTA daily at the 2 and 4 mg OTA levels, respectively, during the last week of experiment. Harvey et al (1987) reported a similar finding in the bursa of Fabricius of chicks hatched from eggs inoculated with OTA. The immunotoxic effects of OTA are mainly characterized by a reduction in the size/ mass of immune system organs such as the spleen, bursa of Fabricius, thymus, lymph nodes, as well as alterations in the function and/or number of immune cells, a depression in host antibody responses, and modulation of the production of cytokines (Al-Anati and Petzinger, 2006).…”
Section: Research Articlesupporting
confidence: 63%
See 2 more Smart Citations
“…This meant that each bird consumed 160 and 320 µg of OTA daily at the 2 and 4 mg OTA levels, respectively, during the last week of experiment. Harvey et al (1987) reported a similar finding in the bursa of Fabricius of chicks hatched from eggs inoculated with OTA. The immunotoxic effects of OTA are mainly characterized by a reduction in the size/ mass of immune system organs such as the spleen, bursa of Fabricius, thymus, lymph nodes, as well as alterations in the function and/or number of immune cells, a depression in host antibody responses, and modulation of the production of cytokines (Al-Anati and Petzinger, 2006).…”
Section: Research Articlesupporting
confidence: 63%
“…To our knowledge, this study is the first to report on the immunotoxic effects of OTA in the progeny of breeder hens fed OTA-contaminated feed. Nevertheless, we are mindful that to provide fuller support to our conclusions/hypotheses here, our future studies will need to verify that: (a) OTA, at the doses used here (and which we recognize are lower than those used in some of the other studies we reference), transfers from the hens to their eggs (and at what concentrations): and, (b) OTA, at those transferred concentrations (i.e., administered to 13-day-old chicken embryos via the chorioallantoic membrane in the manner used by Harvey et al [1987]) induces the effects we are observing in the studies we report here.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This depression in the antibody titers may be due to damage caused by OTA in bursa of Fabricius of chicken embryos, which ultimately resulted in the decrease in the number of immunoglobulinsproducing cells as was reported by Harvey et al (1987) in OTA inoculated chicken embryos. This hypothesis may be further strengthened by the results of a study conducted by Santin et al (2002) in broiler chicks fed OTA at 2 ppm, showing decrease in the mitotic figures in bursa of Fabricius and subsequently depressed humoral immune response, and Moura et al (2004) showed the decrease in the number of lymphocytes in the broiler chicks given intraperitoneal injection of OTA at 0.04 mg/ kg BW.…”
Section: Discussionmentioning
confidence: 57%
“…The decreases in hatchability percentage and BW gain in chicks hatched from eggs obtained from hens kept on OTA-contaminated diet have been reported by Choudhary et al (1971). A decrease in weights of immunological organs in the chicks obtained from hens kept on OTA-contaminated diets and decreases in the number of immunoglobulin(s)-bearing cells in the bursa of Fabricius of chicks hatched from OTA-contaminated eggs were reported by Zahoor-ul-Hassan et al (2011) andHarvey et al (1987), respectively. Though a lot is known about the immunotoxic effects from direct feeding of OTA to various animal species, information regarding the immunological effects of OTA in chicks hatched from eggs contaminated with OTA are scanty and does not cover effects on cellular/humoral immune responses.…”
Section: Research Articlementioning
confidence: 99%